2006
DOI: 10.1007/s10620-006-9378-8
|View full text |Cite
|
Sign up to set email alerts
|

Tricyclic Antidepressants for Chronic Vomiting in Diabetic Patients

Abstract: Chronic vomiting in diabetic patients often is unresponsive to prokinetic agents and poorly explained by delayed gastric emptying or neuropathy. This retrospective study examines clinical response to tricyclic antidepressants, a treatment of reported benefit in nondiabetic patients with unexplained vomiting syndromes. Outcomes were studied in 24 diabetic outpatients who had been treated with tricyclic antidepressants specifically for nausea and vomiting after an unsatisfactory response to prokinetic therapy. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 41 publications
(43 reference statements)
1
58
0
2
Order By: Relevance
“…170 A retrospective study has also suggested that use of tricyclic antidepressants decreased nausea in patients with diabetes mellitus, approximately one-third of whom had delayed gastric emptying. 171 However, in a randomized placebo-controlled trial, use of nortriptyline was not associated with symptomatic improvement in patients with idiopathic gastroparesis. 172 Effects of glycaemia on drug efficacy The prokinetic effects of erythromycin have been shown to be markedly attenuated in the setting of hyperglycaemia.…”
Section: Prokineticsmentioning
confidence: 96%
“…170 A retrospective study has also suggested that use of tricyclic antidepressants decreased nausea in patients with diabetes mellitus, approximately one-third of whom had delayed gastric emptying. 171 However, in a randomized placebo-controlled trial, use of nortriptyline was not associated with symptomatic improvement in patients with idiopathic gastroparesis. 172 Effects of glycaemia on drug efficacy The prokinetic effects of erythromycin have been shown to be markedly attenuated in the setting of hyperglycaemia.…”
Section: Prokineticsmentioning
confidence: 96%
“…28 In a follow-up analysis of 24 diabetics with refractory nausea and vomiting, tricyclics at median doses of 50 mg reduced symptoms in 88% and abolished them in nearly onethird. 29 Twenty-nine percent of patients showed delayed gastric emptying. Taken together, these observations suggested potential utility of tricyclics to reduce nausea, vomiting, and pain in gastroparesis.…”
Section: Symptomatic Management For Gastroparesismentioning
confidence: 99%
“…Bestätigende Studien fehlen allerdings. Trizyklische Antidepressiva, eingesetzt in einer niedrigen Dosierung zur Behandlung von refraktärer Übelkeit und Erbrechen bei DG und IG, zeigten positive Effekte auch im Hinblick auf Abdominalschmerzen [28]. Die bekannten anticholinergen Effekte, z.…”
Section: -Ht 3 -Antagonistenunclassified